The Impact of Credit Rating Changes in Latin American Stock Markets - Abner de Pinho Nogueira Freitas; Andrea Maria Accioly Fonseca Minardi (BAR: Brazilian Administration Review, 2013)
Our objective is to examine whether a rating change or Credit Watch announcement has a significant impact on Latin American stock prices. We conducted an event study to analyze stock market reaction to such news in the four major Latin American economies: Argentina, Brazil, Chile and Mexico. We find similar results to thosepreviously observed in the literature, wherein the impact is quite significant for rating downgrades but less relevant for rating upgrades and Credit Watches. We also run cross section regressions to investigate which variables best explain the impact rating changes announcements have on stock prices in these countries. The results indicate that the most significant variable is the absolute change in the number of notches for downgrades. We conclude that credit ratings are relevant information in Latin America.